The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1980-5918.030.004.ao10
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength, lower extremity functional performance and body composition in elderly women with mild cognitive impairment

Abstract: Introduction: Mild cognitive impairment (MCI) is characterized by subjective memory complaints and is considered an intermediate stage between normal and pathological cognitive function. The decline in cognitive function may be associated with low functional performance and alterations in body composition in older adults. Objective: To assess muscle strength, lower extremity functional performance and body composition in elderly women with MCI. Methods: Forty-three elderly women (aged 60-80 years) participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These findings suggest that coordination abilities, which are essential to performing optimal turns, are not greatly influenced by the presence of cognitive impairments when the individual is relatively young, while they always significantly affect TUG phases, which rely more on postural control and lower limb strength. This is likely due to a reduction in muscle strength (which was previously observed in individuals with MCI of similar age [74,75]), and is also probably influenced by a limited amount of physical activity [76] and poor balance abilities [77]. It was also observed that old-old participants with cognitive impairments required longer times to perform 180° turns, as they probably adopted a cautious strategy to avoid loss of balance and falls.…”
Section: Discussionmentioning
confidence: 74%
“…These findings suggest that coordination abilities, which are essential to performing optimal turns, are not greatly influenced by the presence of cognitive impairments when the individual is relatively young, while they always significantly affect TUG phases, which rely more on postural control and lower limb strength. This is likely due to a reduction in muscle strength (which was previously observed in individuals with MCI of similar age [74,75]), and is also probably influenced by a limited amount of physical activity [76] and poor balance abilities [77]. It was also observed that old-old participants with cognitive impairments required longer times to perform 180° turns, as they probably adopted a cautious strategy to avoid loss of balance and falls.…”
Section: Discussionmentioning
confidence: 74%
“…This may explain why our cross-sectional study suggests a parallel decline in cognition and muscle strength but not in lean mass. However, in a Belgian study of men and women aged 60-80 years, differences in HGS were found between the group with MCI and the normal group; no differences were found in physical performance (gait speed and balance measured by Short Physical Performance Battery) or body composition (muscle and fat mass) 53 .…”
Section: Discussionmentioning
confidence: 79%
“…In this study, bioimpedance changes in the lower extremity were observed and were more significantly associated with MCI than those in the upper extremity. A reduction in physical function in the lower extremity is likely to be related to a higher risk of cognitive decline ( 32 , 33 ); it suggests that more focus should be placed on impedance variable changes in the lower extremity in relation to the early stage of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Mereu et al demonstrated that bioimpedance results obtained for only the right arm would be similar to whole-body composition in patients with AD ( 31 ). Reduction of skeletal muscle mass or muscle strength in the lower limbs was associated with a higher MCI risk in women ( 32 , 33 ), whereas loss of skeletal muscle mass in the upper and lower limbs was associated with a higher risk of MCI in men ( 32 ). Lower extremity skeletal muscle mass was associated with lower cognitive performance and higher cortical beta-amyloid burden ( 34 , 35 ), whereas upper extremity skeletal muscle mass did not show any association ( 34 ).…”
Section: Introductionmentioning
confidence: 99%